Parents’ Perception of Rehabilitation Services for their Children with Special Healthcare Needs in Helena Center in Erbil City (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: First, to determine the socio-demographic characteristics; second, to identify parents’ perceptionof rehabilitation services; and third, to find out the relationship between socio-demographic characteristicsand parents’ perception of rehabilitation services.Methods: A descriptive cross sectional study was carried out. The data were collected from May 2019 toSeptember 2019. A non-probability convenience sampling was used, and sample size of 335 parents whoattending to Helena center for rehabilitation and operation children with special needs in Erbil city wascalculated.Results: The majority (around 80% or more) of the parents had positive attitudes toward the rehabilitationservices provided in the center.Conclusion: Parents of children with special health care needs in Helena Center perceived services providedto their children as family-centered.